THE EFFECT OF WORKING CAPITAL ON FIRM PERFORMANCE - Indah Wahyuni; Seto Sulaksono Adi Wibowo (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2018)
This study aims to examine the effect of working capital on firm performance. To implement the operating activities, the company should be able to manage good working capital. Good working capital management can help to enhance the firm performance in the eyes of investors. In this research, working capital is measured using working capital turnover, inventory turnover, days of supply, and cash conversion cycle as independent variables, while firm performance is measured using net profit margin as the dependent variable. The sample of this research is a manufacturing company listed in Indonesia Stock Exchange (IDX) period 2014-2016. Samples were taken by using purposive sampling and meeting the sample criteria. The anaysis technique used in this research is multiple regression analysis by using t test. The results of the study found that working capital turnover, days of supply, and cash conversion cycle negatively affect the performance of the company. While the variable of inventory turnover shows that inventory turnover has a positive effect on firm performance.